Big Ideas of Primary Mathematics: It's all about connections - Hurst, Chris (World Scientific, 2019)
Big idea thinking provides an opportunity to re-conceptualize how we view and teach primary mathematics. Contemporary curricula continue to be organized in a linear fashion with content allocated to year levels, which encourages a narrow view of what needs to be taught. Big idea thinking has the capacity to change that. The real value of big ideas lies in interpreting the mathematics within them. Big ideas are those which connect mathematical understandings into a coherent whole, and are central to the learning of mathematics. Big ideas comprise a network of ‘little ideas’ or ‘micro-content’ and teachers who think in terms of them are able to look forwards and backwards from their own year level to identify specific content that a student may not know, and to lay the foundations for what the student needs to know next. Big idea teachers are not limited in their thinking by curriculum boundaries. Most importantly, big idea thinking encourages teachers to deconstruct and reconstruct their knowledge. Teachers can actively engage in this by beginning with a mathematical idea such as place value and building a concept map showing the various pieces of ‘micro-content’ that contribute to the development of the concept and considering how the content is connected.